2013
DOI: 10.1186/1471-2334-13-130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial biota in the distal esophagus of Japanese patients with reflux esophagitis and Barrett’s esophagus

Abstract: BackgroundThe distal esophagus harbors a complex bacterial population. We hypothesized that a better understanding of bacterial communities in the esophagus would facilitate understanding of the role of bacteria in esophageal disease. Here, we investigated bacterial composition in the distal esophagus in subjects with a normal esophagus, reflux esophagitis, and Barrett’s esophagus.MethodsTwo biopsy specimens were obtained from the distal esophagus at 1 cm above the gastroesophageal junction under endoscopic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 27 publications
(34 reference statements)
10
112
0
Order By: Relevance
“…As the microbiomes did not differ between GERD and Barrett's esophagus patients, the authors concluded that inflammation and intestinal metaplasia are associated with global alteration of the microbiome in the distal esophagus. Using culture‐independent techniques, Liu et al 44. examined the bacterial composition at the 16S rDNA gene site in subjects with a normal esophagus, reflux esophagitis, or Barrett's esophagus.…”
Section: Microbiome In Esophagitis and Barrett's Esophagusmentioning
confidence: 99%
“…As the microbiomes did not differ between GERD and Barrett's esophagus patients, the authors concluded that inflammation and intestinal metaplasia are associated with global alteration of the microbiome in the distal esophagus. Using culture‐independent techniques, Liu et al 44. examined the bacterial composition at the 16S rDNA gene site in subjects with a normal esophagus, reflux esophagitis, or Barrett's esophagus.…”
Section: Microbiome In Esophagitis and Barrett's Esophagusmentioning
confidence: 99%
“…For example, comparison of the esophageal microbiome among patients with reflux disorders such as reflux esophagitis and Barrett esophagus to that of the microbiome in normal subjects revealed the transformation of the esophageal microbiome to gramnegative bacteria in the disease setting (58)(59)(60). In addition, studies have found association between increased abundance of specific bacterial sequences or bacterial loads and IPF disease progression, including the rate of lung volume decline (61)(62)(63).…”
Section: Pulmonary Perspectivementioning
confidence: 99%
“…The bacterial communities detected in these sites are primarily characterized by members of four phyla: the Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria (113)(114)(115)(116)(117)(118). Recent studies have demonstrated that Campylobacter species, and C. concisus in particular, are among the dominant species present in patients with GERD and BE (113,119).…”
Section: Esophageal Diseasesmentioning
confidence: 99%